Hubungan Pengetahuan Dengan Perilaku Personal Hygiene Saat Menstruasi pada Remaja Putri SMP Negeri 3 Cimahi - Tiara Citra Melinda; Iga Retia Mufti (Journal of Innovative and Creativity (Joecy), 2026)
Background: Personal hygiene during menstruation is an essential part of adolescent girls' reproductivehealth; inadequate knowledge of menstrual personal hygiene increases the risk of reproductive tract disorders.Objective: This study aimed to determine the relationship between knowledge and personal hygiene behaviorduring menstruation among adolescent girls at SMP Negeri 3 Cimahi in 2026. Methods: A quantitativecorrelational-analytic design with a cross-sectional approach was used. The sample consisted of 67 studentsselected through proportionate stratified random sampling. Data were collected using a knowledge and menstrualpersonal hygiene behavior questionnaire and analyzed univariately and bivariately using Fisher's Exact Test.Results: Most respondents had poor knowledge (48 respondents, 71.6%) and poor personal hygiene behavior (33respondents, 49.3%). Bivariate analysis showed a significant relationship between knowledge and personalhygiene behavior (p = 0.001; p < 0.05); respondents with good knowledge tended to show better personal hygienebehavior. Conclusion: There is a significant relationship between knowledge and personal hygiene behaviorduring menstruation among adolescent girls at SMP Negeri 3 Cimahi.